Evaluation of Community-Based Youth Sports Programme in South Africa - Leepile Motlhaolwa; Kim-Tamsin Williams (Universitas Negeri Semarang, 2026)
Sports is seen as a means to develop young people’s social competence and promote a healthy lifestyle and personal development skills, especially values such as leadership, respect, and responsibility. In order to contribute to the development of youth in South Africa, a community-based sports programme, Shongi Soccer Programme (SSP), was implemented by the Philipp Lahm-Stiftung (PLF) in Soul City Township, Johannesburg, South Africa. The evaluation aimed to determine the perceived development outcomes derived from participation in the sports programme and identify strengths and challenges in implementing the sports programme. A survey was conducted with twelve sports programme participants selected through purposive sampling. This was followed by focus group discussions with the same participants, parents, coaches and programme coordinators. The results revealed that the sports programme provided overall positive experiences for youth development, learning and interaction. The participants attributed personal and social development experiences to supportive and positive relationships with the coaches and peers. Furthermore, the results indicate that 67% of participants strongly believed the sports programme was a positive turning point in their lives. These results illustrate that the SSP sports programme has positively impacted the participants' development.